A structural equation model for evaluating user’s intention to adopt internet banking and intention to recommend technology - Mazuri, Abd Ghani; Samar, Rahi; Abdul Hafaz, Ngah (2018)
Although several prior research projects have focused on the factors that impact on the adoption of information technology, there are limited empirical research works that simultaneously capture technology factors (UTAUT2) and customer specific factors (perceived technology security and intention to recommend) helping users adopt internet banking. Thus, the current study aims to develop an integrated technology adoption model with extended UTAUT model and perceived technology security to predict and explain user’s intention to adopt internet banking and intention to recommend internet banking in social networks. A quantitative approach based survey was conducted to collect the data from 398 internet banking users. For statistical analysis, structural equation model (SEM) approach was used. Convergence and divergence with earlier findings were found, confirming that performance expectancy, effort expectancy, social influence, hedonic motivation and perceived technology security had significant influence on user’s intention to adopt internet banking. Additionally, IPMA analysis show that among all constructs hedonic motivation and perceived technology security had the highest impact on user’s intention to adopt internet banking. For researcher, this study provides a basis for further refinement of technology adoption model while for practitioner improving security factor (perceived technology security) may turn users towards adoption of internet banking.